Early-life adversity and later-life mental health: a conditional process analysis of sense of coherence and resilience-related resources - Rohner, Shauna L.; Bernays, Florence; Maercker, Andreas; Thoma, Myriam V. (Frontiers in Child and Adolescent Psychiatry, 2023)
Objective While early-life adversity can have negative effects on health and wellbeing that persist across the lifespan, some individuals show indications of resilience. Resilience can be understood as a dynamic coping process involving the mobilization of resources in response to adversity exposure. Sense of coherence—revised (SOC-R), an ability linked to health maintenance in the face of adversity, may be influential in this process. However, research is lacking on the mechanisms underpinning SOC-R and resilience-related resources and their impact on the (mental) health of individuals exposed to early-life adversity. Therefore, this study examined the role of SOC-R and selected resilience-related resources in the relationship between early-life adversity and later-life health and wellbeing. Method Participants were N = 531 Irish (older) adults (58.2% female, mean age = 59.5 years, range = 50–86 years). Standardized questionnaires assessed retrospective reports of early-life adversity, as well as current physical and mental health, satisfaction with life, SOC-R, and resilience-related resources (self-efficacy, optimism, social support). A multiple mediation analysis tested the indirect effects of the resources and a moderated mediation tested for conditional dependence on SOC-R. Results For mental health and satisfaction with life, significant partial mediations were found for all three resources. Only optimism showed a significant partial mediation for physical health. In the moderated mediation, SOC-R significantly moderated the associations between early-life adversity and self-efficacy (b = .06, t = 3.65, p = .001), optimism (b = .04, t = 2.60, p = .009), and social support (b = .08, t = 3.75, p < .001). The indirect effects were larger at high rather than low SOC-R, indicating that the mediating effects of the resources were greater for individuals with a stronger SOC-R. Conclusion A strong SOC-R may have a beneficial influence on health and wellbeing by mitigating the detrimental effect of early-life adversity on the resources self-efficacy, optimism, and social support. Future avenues for research include the expanded assessment of resources and the potential role of SOC-R in successful ageing through the selection and adaptation of goals and resources into older age. SOC-R may represent a promising target for psychotherapeutic interventions promoting resilience in survivors of early-life adversity.